Different independent associations of depression and anxiety with survival in patients with cancer - Walker, Jane (J Psychosom Res, 2020)
OBJECTIVE: Depression and anxiety have both been reported to predict the worse subsequent survival of people with cancer. However, depression and anxiety are mutually associated and we lack understanding of their independent associations with survival. We therefore aimed to investigate these in a large sample of patients with common cancers. METHODS: We analysed data on 19,966 patients with common cancers (breast, colorectal, gynaecological, lung and prostate) who had attended specialist NHS outpatient clinics in Scotland, UK. Hospital Anxiety and Depression Scale (HADS) data were linked with demographic, cancer and mortality data. We estimated the independent associations of depression (HADS depression score) and anxiety (HADS anxiety score) with survival by fitting (separately for each cancer) Cox proportional hazards models which incorporated cubic splines to allow for non-linear associations. We also adjusted for potential confounders. RESULTS: The median time from HADS completion to death or censoring was 1.9 years. Greater depression was found to be strongly associated with worse survival from all cancers. When adjusted for anxiety, this association remained in males and increased in females. Greater anxiety was also associated with worse survival in nearly all cancers. However, when adjusted for depression, the association of anxiety with worse survival was lost. In females the association reversed direction so that greater anxiety was associated with better survival. CONCLUSION: Although often considered together as aspects of ‘emotional distress’, depression and anxiety have different independent associations with survival in patients with cancer and should therefore be considered separately.